MENGENAL TAFSIR TARJUMAN AL-MUSTAFID KARYA ABDURRAHMAN RAUF AS-SINGKILI - Delima Warna Delima; Nuril Anwairil Nuril (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This article discusses Turjuman al-Mustafid Tafsir written by Abdurrauf as-Singkili as one of the well-known tafsir books in the Nusantara. This study aims to identify the history, interpretation method, and uniqueness of the tafsir in the development of Qur’anic interpretation studies in Indonesia. Turjuman al-Mustafid is a Malay-language tafsir that helped people understand the meaning of the Qur’an at that time. The method used in writing this article is library research by collecting data from books, journals, and other scientific sources. The results of the discussion show that this tafsir had a major influence on the spread of Islamic teachings in the Malay region and became one of the first Malay tafsir studied by society. In addition, the use of simple languagemakes this tafsir easier to understand for various groups of people.